Media Industries in the Digital Era: Analyzing the Democratizing and Decentralizing Effect of Digitalisation on Media Industries - Tas'an, Ayu Kartika Junlianingsih (Journal of International and Local Studies, 2022)
This paper aims to assess the democratizing and decentralising effect of digitalisation towards the media industries. Throughout the history, the relationship between the media industries and technology is a form of an intertwined relationship. A series of developments in the technologies have been affected the production as well as distribution system of the media industries where it brings new opportunities in cultural production making and distribution. The study uses qualitative methodology, particularly study literature to analys in what way digitalisation can be seen as having a democratizing and decentralizing effect on the media industries. The finding in this research demonstrates that (1) digitalisation opens a greater opportunity for the consumer to be an independent content creator (2) digitalisation changes the distribution pattern in media industries where it heavily relies on online platforms (3) Digitalisation still has some limitations, hence, the decentralizing and democratizing effect at some points do not fully achieve.